Diversity and abundance of epiphytic bromeliads in “El Punto ” Santa Catarina Ixtepeji, Oaxaca - Carvente-Acteopan, Sabina; Pérez Olvera, Ma. Antonia; Flores-Cruz, María; Navarro-Garza, Hermilio; Flores-Hernández, Noé (Revista Mexicana de Ciencias Agrícolas, 2017)
Bromeliads are plants that grow in forests and jungles of  the American continent. In Mexico the reported bromeliads  surpass 363 and Oaxaca has 189 of them. The municipality  of Ixtepeji and its agencies including “El Punto” in Oaxaca,  take advantage of epiphytic bromeliads. Since 2008 they have  a UMA, where their members collect in specific areas. In  order to determine the diversity and abundance of bromeliads  as ecological indicators of forest management, a targeted  sampling was carried out during 2015 in four bromeliad  utilization areas: La Cruz de Yovaneli, La Curva de San Miguel,  Reynoso and La Petenera. 300 trees were selected in each  zone of which 87 are oak ( Quercus sp.), 32 pine ( Pinus sp.)  and one  Bursera sp tree. In the forophytes, bromeliad species  were quantified. Most bromeliads diversity and abundance   of species was observed in   Tillandsia (11 sp.) genus, with  specificity location of at least two species per area. The oak was  the forophyte that showed the greatest diversity and abundance  of bromeliads. The Shannon diversity index was average in the  Curva de San Miguel and Reynoso areas (1.5 and 1.3) and low  for La Cruz de Yovaneli and La Petenera areas (0.6 and 0.4).
Keywords: abundance, diversity, phorophyte, Shannon index